Financial Stability, Fiscal Sustainability and Changes in Debt Structure after an Economic Downturn - Rutkauskas, Virgilijus (Ekonomika, 2015)
In this paper, the author finds links among changes in private and public debt during economic downturn and discusses their financial stability and fiscal sustainability consequences. Financial deepening in years before the economic downturn resulted in the growth of indebtedness among agents within economy that sustained afterwards. The European Union has not become less indebted during and after the economic meltdown, but the structure of debt holders has changed. The growth of private debt in the upturn phase resulted in a qualitatively new level of economy. However, in order to sustain the same level after the economic downturn, the public sector was forced to increase its debt. As a result, interactions among financial stability and fiscal sustainability have become more pronounced as monetary financial institutions experienced deleveraging from the private sector and an increase of leverage from the public sector. Thus, the financial stability and fiscal sustainability nexus is analysed by employing flow-of-funds data that show balanced interlinkages among real and financial flows. Recent discussions on sovereign debt instability and suggestions to diminish public debt whatever it costs lack an appropriate answer who will replace it as the flow-of-funds in economy is always in balance.
Keywords: financial stability; fiscal sustainability; flow-of-funds analysis; interconnectedness; balance sheet approach